2012
DOI: 10.1380/ejssnt.2012.33
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Biodistribution and Biocompatibility of Gelatin-Coated Copper Nanoparticles and Naked Copper Oxide Nanoparticles

Abstract: In this study, we investigated the biocompatibility of gelatin-coated copper nanoparticles. To estimate their cytotoxicity, the coated copper nanoparticles were exposed to osteoblastic cells. The cell proliferation remained above 80% even when the particles concentration increased. When uncoated copper oxide nanoparticles were exposed to the cells, the proliferation ratio rapidly decreased with the concentration reaching 20% under the same conditions. To determine their biodistribution, the nanoparticles were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 21 publications
0
3
0
Order By: Relevance
“…In our previous study, cupper nanoparticles coated by gelatin was synthesized and then exposed to MC3T3-E1 cells. Compared with CuO nanoparticles, the viability increased drastically [12]. Recently, we succeeded in time-lapse observation of cell dynamic behavior under nanoparticles exposure.…”
Section: Discussionmentioning
confidence: 99%
“…In our previous study, cupper nanoparticles coated by gelatin was synthesized and then exposed to MC3T3-E1 cells. Compared with CuO nanoparticles, the viability increased drastically [12]. Recently, we succeeded in time-lapse observation of cell dynamic behavior under nanoparticles exposure.…”
Section: Discussionmentioning
confidence: 99%
“…Copper electrodes are often used to manufacture electrochemical sensing devices [48][49][50][51] (e.g., glucose sensors) and as a base for skin electrodes [52][53][54]. However, due to the high toxicity of copper and copper oxide [55][56][57], copper electrodes can not replace expensive noble metal electrodes in many important fields of bioelectronics such as impedance-based in vitro and in vivo cell and tissue studies (for example, using the ECIS method [6]), neuronal electrophysiological investigation with multi-electrode arrays [34], etc.…”
Section: Introductionmentioning
confidence: 99%
“…Surface modification has been used as a strategy for improving cytocompatibility of materials, with several reports of cytocompatibility improvement because of surface modification. For example, Liu et al [10] reported that surface modification of carbon nanotube with carboxyl group improved its biocompatibility, while Abe et al [11] reported that biocompatibility of copper nanoparticles was improved using a gelatin coating. Yang et al [12] reported that poly(dimethylsiloxane) modified with polysaccharides showed higher cytocompatibility than the unmodified poly(dimethylsiloxane).…”
Section: Introductionmentioning
confidence: 99%